Sleep deprivation increases the costs of attentional effort: Performance, preference and pupil size. (4th February 2019) - Massar, Stijn A.A.; Lim, Julian; Sasmita, Karen; Chee, Michael W.L.
Abstract: Sleep deprivation (SD) consistently degrades performance in tasks requiring sustained attention, resulting in slower and more variable response times that worsen with time-on-task. Loss of motivation to exert effort may exacerbate performance degradation during SD. To test this, we evaluated sustained performance on a vigilance task, combining this with an effort-based decision-making task and pupillometry. Vigilance was tested at rest and after sleep deprivation, under different incentive conditions (1, 5 or 15 cents for fast responses). Subsequently, preference measures were collected from an effort-discounting task, in which a commensurate reward was offered for maintaining attentional performance for different durations (1, 5, 10, 20 or 30 min). Vigilance was impaired during SD, in a manner modulated by reward value. Preference metrics showed that the value of available rewards was discounted by task duration, an effect compounded by SD. Pupillometry revealed that arousal was modulated during SD in a value-based manner, and moment-to-moment fluctuations in pupil diameter were directly predictive of performance. Together, these data demonstrate that attentional performance can be interpreted within a value-based effort allocation framework, such that the perceived cost of attentional effort increases after sleep deprivation. Highlights: Sleep deprivation (SD) affects attentional performance by reducing cognitive resources. Decline in motivation after SD may reduce the effort allocated to task performance. We combined performance, pupillometric and preference metrics to study effort allocation. All metrics showed a shift towards more selective allocation of attentional effort after SD. Exerting effort thus appears to be more costly after SD.